Sensitivity of Mountain Hydroclimate Simulations in Variable‐Resolution CESM to Microphysics and Horizontal Resolution. (30th June 2018) - Rhoades, Alan M.; Ullrich, Paul A.; Zarzycki, Colin M.; Johansen, Hans; Margulis, Steven A.; Morrison, Hugh; Xu, Zexuan; Collins, William D.
Abstract: Mountains are natural dams that impede atmospheric moisture transport and water towers that cool, condense, and store precipitation. They are essential in the western United States where precipitation is seasonal, and snowpack is needed to meet water demand. With anthropogenic climate change increasingly threatening mountain snowpack, there is a pressing need to better understand the driving climatological processes. However, the coarse resolution typical of modern global climate models renders them largely insufficient for this task, and signals a need for an advanced strategy. This paper continues the assessment of variable‐resolution in the Community Earth System Model (VR‐CESM) in modeling mountain hydroclimatology to understand the role of grid‐spacing at 55, 28, 14, and 7 km and microphysics, specifically the Morrison and Gettelman (2008, MG1, https://doi.org/10.1175/2008JCLI2105.1 ) scheme versus the Gettelman and Morrison (2015, MG2, https://doi.org/10.1175/JCLI-D-14-00102.1 ) scheme. Eight VR‐CESM simulations were performed from 1999 to 2015 with the F_AMIP_CAM5 component set, which couples the atmosphere‐land models and prescribes ocean data. Refining horizontal grid‐spacing from 28 to 7 km with the MG1 scheme did not improve the simulated mountain hydroclimatology. Substantial improvements occurred with the use of MG2 at grid‐spacings ≤ 28 km compared to MG1 as shown with subsequent statistics. Average SWE bias diminished by 9.4X, 4.9X, and 3.5X from 55 to 7 km. The range in minimum (maximum) DJF spatial correlations increased by 0.1–0.2 in both precipitation and SWE. Mountain windward/leeward distributions and elevation profiles improved across hydroclimate variables, however not always with model resolution alone. Disconcertingly, all VR‐CESM simulations exhibited a systemic mountain cold bias that worsened with elevation and will require further examination. Key Points: As long as diagnostic precipitation in microphysics schemes is used, model grid‐spacing provides essentially no benefit at scales <28 km Spatial distributions in mountain hydroclimatology improved using a prognostic precipitation microphysics scheme and refined grid‐resolution A mountain cold bias was found across all eight variable‐resolution Community Earth System Model simulations from 55 to 7 km grid‐spacing